The EAP competencies in a group case study project as revealed by a task analysis - Smith, Ann F.V.; Thondhlana, Juliet (Elsevier, 2015)
In EAP in the UK, preparing students for real academic assignments in higher education is a central focus. As assessed group project assignments are becoming increasingly popular in UK universities, this study investigates the demands of a first year undergraduate group case study project in business. Task based syllabuses are common in EAP, so a task analysis framework developed from task-based learning was used to examine the project documents, the requirements of the project and its chain of integrated tasks. The findings show that the project document was dense and multifaceted and the integrated tasks were highly interactive and extremely complex in terms of cognitive and code complexity and communicative stress. In this particular instance, the difficulties faced by international students are examined and the demands in terms of team dynamics and management,language and EAP competencies are identified. The study recommends that EAP practitioners need to be more aware of the academic competencies and group dynamics involved in both complex group projects and case study projects in the receiving disciplines and programmes.